On Leading Meetings: Linking Meeting Outcomes to Leadership Styles. (May 2017) - Odermatt, Isabelle; König, Cornelius J.; Kleinmann, Martin; Nussbaumer, Romana; Rosenbaum, Amanda; Olien, Jessie L.; Rogelberg, Steven G.
Leading meetings represent a typically and frequently performed leadership task. This study investigated the relationship between the leadership style of supervisors and employees' perception of meeting outcomes. Results showed that participants reported greater meeting satisfaction when their meeting leader was assessed as a considerate supervisor, with the relationship between considerate leadership style and meeting satisfaction being mediated by both relational- and task-oriented meeting procedures. The results, however, provide no support for initiating structure being associated with meeting effectiveness measures. More generally, the findings imply that leadership behavior is a crucial factor in explaining important meeting outcomes.